Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/1759720x15579189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of denosumab on bone density, mass and strength in women with postmenopausal osteoporosis

Abstract: Denosumab is a human monoclonal antibody which specifically blocks receptor activator of nuclear factor κB ligand and is a very potent antiresorptive drug. Its efficacy in reducing the risk of vertebral, hip and nonskeletal fracture has been proven in a large prospective, randomized multicenter study of 7808 postmenopausal women with osteoporosis [Fracture Reduction Evaluation of Denosumab in Osteoporosis Every 6 Months (FREEDOM) trial]. Denosumab causes somewhat greater increases in bone mineral density (BMD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…In another study, Zanchetta et al showed significant improvement in BMD and bone microarchitecture as detected by high-resolution peripheral quantitative computed tomography after one year of GFD with concomitant calcium and vitamin D supplementation [6]. Overall, the gain in BMD seen in our patient at both the lumbar spine and total hip is more than the average gain reported with oral bisphosphonates over three years [12].…”
Section: Discussionsupporting
confidence: 50%
“…In another study, Zanchetta et al showed significant improvement in BMD and bone microarchitecture as detected by high-resolution peripheral quantitative computed tomography after one year of GFD with concomitant calcium and vitamin D supplementation [6]. Overall, the gain in BMD seen in our patient at both the lumbar spine and total hip is more than the average gain reported with oral bisphosphonates over three years [12].…”
Section: Discussionsupporting
confidence: 50%
“…DMab treatment for up to 8 years significantly decreased bone turnover (6), increased bone mineral density (BMD)(7), improved bone microstructure of both cortical and trabecular bone (7, 8), and reduces the risk of bone fracture and osteoporosis (3, 5, 9-12). Bone biopsies confirmed potent and sustained effects of DMab on bone quality with continuous DMab treatment for 5-8 years (3, 4). The beneficial effects of DMab, however, can be fully reversed at the tissue level within 2 years of discontinuation, indicating that the skeletal effects of DMab are directed towards regulation of bone turnover to inhibit resorption and maintain bone mineral density (BMD).…”
Section: Introductionmentioning
confidence: 77%
“…However, DMab, but not bisphosphonates, significantly suppressed bone metabolism in a cohort of Japanese RA patients not previously treated for osteoporosis. These findings suggest distinct cellular mechanisms underlying DMab- and bisphosphonate-based RA therapy (4, 58). DMab exerts its protective effects likely through the WNT/β-catenin signaling pathway via regulating DKK-1 (25, 59).…”
Section: Denosumab - Current Indicationsmentioning
confidence: 93%
“…Kostenuik et al have stated that administration of high doses of Denosumab in adult ovariectomized cynomolgus monkeys (up to 16 months) significantly improved the structural bone strength and bone mass (Kostenuik et al, 2011). In a randomized placebo-controlled and FREEDOM trial, Denosumab treatment to postmenopausal women with osteoporosis, caused significant reduction in risk of non-vertebral, vertebral, and hip fractures by 20, 68, and 40% (P < 0.001), respectively, however it increased the risk of cellulitis (Cummings et al, 2009;Bell and Bell, 2011;Törring, 2015). According to the literature, Denosumab worked better than risedronate, raloxifene, and alendronate, at diminishing the occurrence of vertebral fractures (Freemantle et al, 2013).…”
Section: Denosumabmentioning
confidence: 99%